Baseline Leptin/Adiponectin Ratio is a Significant Predictor of BMI Changes in Children/Adolescents after Intensive Lifestyle Intervention - Pejsova, Hana; Hubacek, Jaroslav A.; Zemankova, Petra; Zlatohlavek, Lukas (Experimental and Clinical Endocrinology & Diabetes, 2019)
Introduction Abdominal obesity is a strong cardiometabolic risk factor that often occurs as early as in childhood. The negative effect of abdominal obesity on the metabolism is partially mediated by changes to the production of the major adipocyte hormones leptin and adiponectin. Leptin/adiponectin imbalance is associated with increased risk of developing obesity and type 2 diabetes mellitus.Aim To determine whether leptin, adiponectin and the leptin/adiponectin ratio are significant predictors of body weight loss in intensively treated children/adolescents.Methods 183 paediatric overweight or obese patients (71 boys and 112 girls), aged 7–16 years, were enrolled in a one-month intensive lifestyle intervention programme. Participants reduced their energy intake and engaged in a supervised exercise programme consisting of 5 physical activity units per day. The subjects were examined both before and after the intervention.Results The mean BMI decrease achieved was−2.38±0.07 kg/m² (P<0.01). The decrease in plasma leptin concentration was−16.59±0.84 ng/mL (P<0.001) and CRP−0.38±0.04 mg/L (P<0.001). Changes in adiponectin concentrations were not statistically significant. The baseline leptin/adiponectin ratio was a significant predictor of decreases in body weight (P<0.005), BMI (P<0.0001) and waist circumference (P<0.05).Conclusion The leptin/adiponectin ratio at baseline may be a useful predictor of results from interventions focused on decreasing BMIs in children/adolescents.
Keywords: abdominal obesity; leptin; adiponectin; CRP; cardiovascular risk